PENGARUH PENGAWASAN INTERNAL, PEMAHAMAN SISTEM AKUNTANSI KEUANGAN DAN PENGELOLAAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN (Studi pada Kantor DPPKAD Kabupaten Boyolali) - Risdhayanti Nur Sholikah, Dewi Saptantinah Puji Astuti & Muhammad Rofiq Sunarko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this study was to analyze the significance of the effect of internal control, understanding of financial accounting system and financial management partially or simultaneously to the quality of local government financial statements in Boyolali. The research method used survey method, the type of data used quantitative and qualitative data, the data source used primary data and secondary data. The population in this study were all employees in the office DPPKAD Boyolali as many as 84 people, the number of samples are 68 used simple random sampling method. Methods of data collection using questionnaires. Data analysis technique used to test the validity, reliability test, classic assumption test, path analysis. In conclusion, there is a significant influence independent variables are internal control, understanding of financial accounting system and financial management partially or simultaneously to the quality of financial reports in local government Boyolali as dependent variableKeywords: internal control, understanding of financial accounting system, financial management, the quality of financial